2013
DOI: 10.1016/j.jocn.2012.05.037
|View full text |Cite
|
Sign up to set email alerts
|

A streamlined protocol for the use of the semi-sitting position in neurosurgery: A report on 48 consecutive procedures

Abstract: The semi-sitting position has lost favor among neurosurgeons partly due to unproven assumptions of increased complications. Many complications have been associated with this position; the most feared: venous air embolism and paradoxical air embolism. We report on this retrospective study of the outcome over 4 years of 48 neurosurgical patients operated on consecutively using a standardized protocol: 41 (85%) in the semi-sitting position, and seven (15%) in the prone position. Procedures included: tumor resecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 24 publications
1
34
0
4
Order By: Relevance
“…In a sitting position operation, in addition to the special management of patients' tracheal intubation, the literature that reported serious complications may occur such as an air embolism 26 . But a recent retrospective study of the outcome of neurosurgical patients operated in a semi-sitting position showed that clinically significant venous air embolism was rare (4.9%) and nonfatal 27 . Moreover, in our study there was no additional morbidity.…”
Section: Considerations and Complicationsmentioning
confidence: 99%
“…In a sitting position operation, in addition to the special management of patients' tracheal intubation, the literature that reported serious complications may occur such as an air embolism 26 . But a recent retrospective study of the outcome of neurosurgical patients operated in a semi-sitting position showed that clinically significant venous air embolism was rare (4.9%) and nonfatal 27 . Moreover, in our study there was no additional morbidity.…”
Section: Considerations and Complicationsmentioning
confidence: 99%
“…Nevertheless, in neurosurgery, the sitting position is usually linked with complications (venous air embolism in particular), although recent studies demonstrated decreased rates of complications in patients undergoing surgeries in the sitting position. [13,14] Nevertheless, anesthesiologists and surgeons continue to avoid this position. [15] Up to date, no reports of patients undergoing craniostomy in the sitting position for CSDH have been published.…”
Section: Introductionmentioning
confidence: 99%
“…3 The risk of developing a VAE exists for all kinds of neurosurgical procedures; however, its incidence is higher for procedures requiring the patient to be in a sitting 4 or semisitting position. 5,6 The incidence of air embolism in the sitting position is variable but has been described in up to 45% of the cases. 7 It may also occur with the patient in lateral decubitus, supine or prone position.…”
Section: Introductionmentioning
confidence: 99%